Time periodic boundary value Stokes problem in a domain with an outlet to infinity - Juodagalvytė, Rita; Kaulakytė, Kristina (Nonlinear Analysis: Modelling and Control, 2018)
We prove the existence of a unique weak solution to the time periodic nonhomogeneous boundary value Stokes problem in a domain having an outlet to infinity.